Pembuatan Sabun Padat dari Minyak Kelapa dengan Penambahan Ekstrak Buah Pare (Momordica Charantia L) sebagai Antioksidan Menggunakan Metode Cold Process - Andi Nurpati Panaungi; Hasma Hasma; Indriana Boroallo (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Currently the use of soap as a skin cleanser is increasingly popular and the variety of types, colors, aromas, and benefits offered by commercially available soaps show their diversity. Bitter gourd (Momordica charantia L) is a plant known as a plant that has a bitter taste, but is widely consumed by Indonesian people. Bitter gourd (Momordica charantia L) is also known to contain flavonoid polyphenols and vitamin C, which act as natural antioxidants. Antioxidants such as tannins, saponins, steroids, and terpenoid hormones. The purpose of this study was to determine the process of making solid soap from coconut oil with the addition of bitter melon extract (Momordica charantia L) as an antioxidant using the cold process method. This type of research is experimental using a simple formula design. The research phase includes sample management, preparation of preparations, and product analysis testing. The test includes an organoleptic test where the results of the data obtained are solid soap with brown spots, distinctive aroma, smooth texture, and square shape. The pH test is alkaline, namely F1 = 10.2 F2 = 10.3 F3 = 10.4. The foam height test has a height of F1 = 4.5 mm, F2 = 7 mm, F3 = 8 mm. test water content as much as 15%. From the results of the research that has been done, it can be concluded that the soap formula made meets the requirements of the SNI standard that is safe for use on human skin.